2009
DOI: 10.4319/lom.2009.7.848
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cooking spices in natural waters

Abstract: An isolation and quantification technique is presented for the analysis of semi-volatile spices and scents in aquatic waters including thymol, eugenol, limonene, carvacrol, vanillin, and cinnamaldehyde. Compounds are isolated from natural waters by solid phase extraction onto Waters Oasis HLB columns and eluted into ethyl acetate. Recovery efficiencies are >70% for most target compounds. Comparison with liquid-liquid extraction and C-18 solid phase extraction indicates that HLB cartridges are more robust and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 18 publications
2
13
1
Order By: Relevance
“…Dissolved lignin samples were filtered through 142 mm diameter Whatman GF/F glass fiber filters and 142 mm Pall Supor membrane filters (0.2 μm pore-size), acidified to pH 2 with HCl, extracted at 3 mL/ min on Waters Oasis HLB solid phase extraction cartridges (6 cm 3 volume, 200 mg sorbent), and frozen (Keil and Neibauer, 2009). 500 to 1000 mL of water was passed through each cartridge depending on the abundance of DOC.…”
Section: Molecular Measurementsmentioning
confidence: 99%
“…Dissolved lignin samples were filtered through 142 mm diameter Whatman GF/F glass fiber filters and 142 mm Pall Supor membrane filters (0.2 μm pore-size), acidified to pH 2 with HCl, extracted at 3 mL/ min on Waters Oasis HLB solid phase extraction cartridges (6 cm 3 volume, 200 mg sorbent), and frozen (Keil and Neibauer, 2009). 500 to 1000 mL of water was passed through each cartridge depending on the abundance of DOC.…”
Section: Molecular Measurementsmentioning
confidence: 99%
“…In this study, we build on previous findings from Dittmar et al (), Spencer et al (), and Keil and Neibauer () to better explore the effects of DOM isolation techniques on the optical properties and quantification of dissolved LOPs, naturally free‐lignin phenols, and the resultant diagnostic ratios. More specifically, and for the first time to our knowledge, we investigate the fractionation effects of C‐18, HLB, and PPL cartridges on the abundance and distribution of free/unbound and polymeric lignin phenols within both riverine and coastal/saline matrices.…”
mentioning
confidence: 97%
“…Recent work has shown that the extraction of dissolved organic matter (DOM) via solid‐phase extraction (SPE) is biased toward specific functional groups, molecular size and/or conformations, thereby affecting all subsequent analyses, such as bulk carbon, biomarker, and spectroscopy measurements (Spencer et al ; Chen et al ; Raeke et al ; Li et al ). Much of this previous work has been on the bulk carbon of DOM, with very few studies examining fractionation effects on naturally occurring dissolved lignin phenols and lignin oxidization products (LOPs) (Keil and Neibauer ; Spencer et al ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of literature and existing methods Keil and Neibauer, 2009;Peck, 2006;Simonich et al, 2000;Vecchiato et al, 2015), different solvents and aliquots were tested for the elution of the FMs from the SPE cartridges and the final procedure derives from the combination of the most effective ones. Cartridges were not dried under vacuum in order to prevent possible losses of the more volatile analytes.…”
Section: Sample Processingmentioning
confidence: 99%